Neutrophil and lymphocyte ratio in craniocervical artery dissection and prognostic correlations of the blood biomarkers - AKDENİZ, ESRA; ÖMERCİKOĞLU ÖZDEN, HATİCE; BALTACIOĞLU, FEYYAZ; MİDİ, İPEK (My University, 2022)
Background & Objective: The aim of this study was to investigate the relationship of neutrophil to lymphocyte ratio (NLR) and other blood cells markers in craniocervical artery dissection patients and the dynamic changes of these biomarkers during the disease course, and effects on prognosis of the patients. Method: Cranial MR imaging, cranial and cervical MR angiography and DSA were examined, and diffusion weighted imaging (DWI) was performed to show the acute lesion(s). Results: Forty-six patients with craniocervical artery dissection were included in this study; they had a mean age of 42 years. Almost 60% of the patients (n=27) were admitted during acute state. Almost 2/3 of cases had extracranial dissection (n=31) and nearly 40% of the patients (n=18) had trauma. Neutrophil to lymphocyte ratio (NLR) was observed to be higher in the acute phase of the disease while the ratio decreased in the chronic phase. Low hemoglobin, high lymphocyte and a high NLR were found to have a negative correlation with the National Institutes of Health Stroke Scale (NIHSS). Conclusion: Elevation of neutrophil was higher in acute craniocervical artery dissection as a marker of acute inflammatory response. High NLR, low hemoglobin and high eosinophil levels were associated with worse prognosis and functional outcomes.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Neurology (clinical); Life Sciences; Craniocervical artery dissection; neutrophil to lymphocyte ratio (NLR); prognosis; ISCHEMIC-STROKE; TO-LYMPHOCYTE; PREDICTOR; INFLAMMATION; ASSOCIATION; Craniocervical artery dissection; neutrophil to lymphocyte ratio (NLR); prognosis